Electron-positron pair production in low-energy heavy-ion collisions. (July 2015) - Maltsev, I A; Shabaev, V M; Tupitsyn, I I; Bondarev, A I; Kozhedub, Y S; Plunien, G; Stöhlker, Th
Synopsis: A method for calculations of pair production in low-energy collisions of heavy ions is developed. The approach is based on the numerical solving of the two-center time-dependent Dirac equation in the monopole approximation. Employing the developed method the positron energy spectra and the numbers of the created pairs are calculated for the symmetric collisions of bare nuclei with different values of the impact parameter and the nuclear charge. In order to investigate the role of the spontaneous pair production the different subcritical and supercritical scenarios are considered.